The challenge of leading with multiple and severe gastrointestinal complications in a patient with systemic sclerosis - Raquel Batista; Lara Adelino; Cristina Lopes; Maria de Fátima Pimenta (Galicia Clínica, 2018)
Systemic sclerosis (SSc) is a multisystem autoimunne disorder that involves the gastrointestinal tract in more than 90% of patients. The various gastointestinal complications result in a numerous presentations that impair oral intake and fecal continence, and consequently have an adverse effect on the patients quality of life. Malnutrition from significant intestinal envolvement portends a poor prognosis in systemic sclerosis and is often a callenging problem to manage. We report a case of systemic sclerosis with multiple and severe gastrointestinal manifestations , including intestinal pseudo-obstrution , malabsorption and esophageal candidiasis.